Understanding the Impacts of China’s Belt and Road Initiative (BRI) over the Program for Infrastructure Development in Africa (PIDA) (2013-2023) - Muhammad Amjad Raza; Dr. Abdul Basit Khan (Pakistan Social Sciences Review, 2024)
To fulfil her ever-growing commercial and economic needs, the 21st century China is undertaking multiple assignments and involved in several mega developmental projects across the globe nevertheless the South Asia, Central Asia and African Union (AU) have been enjoying primary importance in this regard and have attracted billions of dollars during the term of current Chinese President Xi Jinping. Keeping the preceding fact in view, the instant study focuses on the engagements of China with the member states of AU to understand the nature and scope of various projects being undertaken to increase the regional and intercontinental connectivity aligned with Belt & Road Initiative (BRI) and the Program for Infrastructure Development in Africa (PIDA) during 2013-2023 across five African geographical regions. By qualitatively evaluating relevant academic literature, project reports, and financial documents, it finds that China and the AU are mutually engaged in infrastructure development, establishing trade routes along with economic zones to promote industrialization and ensure economic growth. It establishes that substantial Chinese investment in the length and breadth of AU has contributed to regional integration and social prosperity whereas China, in return, has secured a deep-rooted as well as long-lasting penetration into the region which, for centuries, had commonly been dubbed as the dark continent.
Keywords: Belt and Road Initiative (BRI); Program for Infrastructure Development in Africa (PIDA); China-African Union Relations